2006
DOI: 10.1207/s15327957pspr1001_3
|View full text |Cite
|
Sign up to set email alerts
|

The Paranoid Optimist: An Integrative Evolutionary Model of Cognitive Biases

Abstract: Human cognition is often biased, from judgments of the time of impact of approaching objects all the way through to estimations of social outcomes in the future. We propose these effects and a host of others may all be understood from an evolutionary psychological perspective. In this article, we elaborate error management theory (EMT;Haselton & Buss, 2000). EMT These two wisdoms seem contradictory. The first urges caution, whereas the second reminds us that we have nothing to lose and should throw caution t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
635
2
10

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 707 publications
(670 citation statements)
references
References 120 publications
(170 reference statements)
23
635
2
10
Order By: Relevance
“…Specifically, we found that even while self-esteem decreased, positive beliefs about the self were maintained following the capacity-rejection manipulation. Positive beliefs about the self are functional (Haselton & Nettle, 2006;Kurzban & Aktipis, 2006Trivers, 2000), and such beliefs may be especially important following capacity rejection to motivate approach behavior. Indeed, there is experimental evidence that rejection increases people's motivation to forge new social bonds (Maner et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, we found that even while self-esteem decreased, positive beliefs about the self were maintained following the capacity-rejection manipulation. Positive beliefs about the self are functional (Haselton & Nettle, 2006;Kurzban & Aktipis, 2006Trivers, 2000), and such beliefs may be especially important following capacity rejection to motivate approach behavior. Indeed, there is experimental evidence that rejection increases people's motivation to forge new social bonds (Maner et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, holding overly positive beliefs about one's qualities (i.e., ''positive illusions'') has been proposed to be an adaptive tendency, both psychologically and reproductively (Haselton & Nettle, 2006;Taylor & Brown, 1988). Holding extreme self-beliefs (narcissism) may be self-defeating and lead to aggression.…”
mentioning
confidence: 99%
“…For instance, foods, animals, and body products -core disgust elicitors -are all potentially infectious. Similarly, three of the four elicitors of animal reminder disgust (dead bodies, individuals with poor hygiene, and body envelope violations) are also sources of contagion -even objectively non-infectious objects conceptualized within the animal reminder domain (e.g., amputated limbs, congenital deformities) elicit a disease-avoidance response (Schaller & Duncan, 2007;Haselton & Nettle, Three domains of disgust 11 2006; Kurzban & Leary, 2001;Park, Schaller, & Faulkner, 2003). What were originally viewed as independent categories of disgust elicitors are more parsimoniously explained as related disgust elicitors within a broader domain of pathogen disgust.…”
Section: Pathogen Disgustmentioning
confidence: 99%
“…Followership decisions, however, are very seldom made under completely clear contextual circumstances. To cope with uncertainty, theories about adaptive decision-making under uncertainty-such as life history theory (e.g., Nettle, Frankenhuis, & Rickard, 2013) and error-management theory (Haselton & Nettle, 2006;Tooby & Cosmides, 1990)-suggest that individuals rely on "forecasts" that reflect internally stored information about the world. To form adaptive followership decisions under uncertainty, it is therefore likely that decisions-in addition to contextual information-reflect individuals' default expectations or "bets" about social environments and the problems inherent in them.…”
Section: Mechanisms For Assessing Problem-context: the Role Of Politimentioning
confidence: 99%